What lay illness narratives reveal about AIDS-related stigmatization - Adelia Carstens (Communicare)
The main purpose of this contribution is to broaden the understanding of variables surrounding the stigmatization of people living with HIV/AIDS by analyzing a corpus of Afrikaans-speaking teenagers' narratives on HIV/AIDS. Support is given for the hypothesis that lay illness narratives are interdiscursive constructions, based on media discourses about HIV/AIDS, and mapped against the mental schemas of the narrator's own life and identity. Instances of convergence as well as dissonance between reported illness narratives (media narratives) and lay illness narratives are highlighted, with specific reference to the clustering of stereotypical features, constituting three archetypes of people living with HIV/AIDS, namely the AIDS carrier, the AIDS victim and the AIDS survivor.